Quantitative analysis of macrobenthic soft-bottom assemblages in South Shetland waters (Antarctica) - Saiz-Salinas, José Ignacio; Ramos, Ana; García, Francisco José; Troncoso, Jesús; San-Martín, Guillermo; Palacín, Cruz (Polar Biology, 1997)
Macrobenthic assemblages were investigated at 26 stations located around Livingston Island, Deception Island and the Bransfield Strait at depths ranging from 42 to 671 m. Representatives of 30 major taxa were found. The maximal density was 5,260 specimens·m−2 at Livingston Island; the mean abundance per station ranged from 160 to 4,380 specimens·m−2. The total biomass of the macrozoobenthos declined with depth, with mean values of 3,201 g·m−2 at shallower depths (< 100 m) and 210 g·m−2 further down (> 100 m). After multivariate analysis (cluster analysis, MDS) based on Bray-Curtis dissimilarities, most stations could be assigned to one of three groups on the basis of distinct biomass differences between sites. The first cluster with a rich Ascidiacea biomass is common on shallower bottoms. The second, with Ophiuroidea as a characteristic group, is common on deeper bottoms. The absence of an ‘indicator’ taxon is characteristic of the remaining cluster of those stations with the lowest biomass values. No significant correlations were detected between macrobenthic biomass and any sediment parameters measured, probably because part of the benthos (i.e. the epifauna) could be better explained by the coupling with a highly productive water column. The role of the epi-infauna sensu Gallardo as the main factor structuring benthic assemblages in the investigated area is discussed. SI